News coverage on female presidential candidates: a proposal from framing - Álvarez-Monsiváis, Edrei (2019)
The paper presents a review of the literature of news coverage on female presidential candidates. For this purpose, seven coverage frames  are included: a) visibility, b) gender reiteration, c) mediation of the intimate sphere, personality, d) thematic agenda, e) tonality and f) particularities of the media. Finally, an operationalization proposal is formulated for each of the frames that could be used in future research that addresses these political figures. It is concluded that women are represented from their intimate sphere and femininity, characteristics that are far from being culturally appropriate for debate in the public and political arena.